2002
DOI: 10.1002/1521-3994(200210)323:5<494::aid-asna494>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The dynamics of a radiating perfect fluid universe coupled with scalar field and heat flux are studied in the nonstatic Gödel‐type universe including the cosmological constant and obtained some exact solutions of Einstein field equations. The solutions have nonzero expansion, shear, and rotating universe. Various physical and geometrical properties of the model are also discussed and the temperature distribution is also given explicitly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Only if your German diction is that of the elder author. Tarhan (2002) mentions the inclusion of shear and rotation, however, which ought to make the process easier.…”
Section: Their Worlds and Welcome To Themmentioning
confidence: 99%
“…Only if your German diction is that of the elder author. Tarhan (2002) mentions the inclusion of shear and rotation, however, which ought to make the process easier.…”
Section: Their Worlds and Welcome To Themmentioning
confidence: 99%
“…In 2003 Mohanty et al [14] studied LRS Bianchi I type universe with attractive massive scalar field in the case of source density model and they have showed that how the dynamical importance of the scalar field and shear change in the course of evolution [14]. Particle physics and high energy astrophysical observations show that the universe is rotating [16][17][18][19][20][21]. A rotating universe with vanishing expansion and shear appeared with the advent of Gödel's universe [20,22].…”
mentioning
confidence: 99%